Prevalence, incidence and presence of comorbidities in patients with prurigo and pruritus in Germany: A population‐based claims data analysis. (24th July 2021) - Augustin, M.; Garbe, C.; Hagenström, K.; Petersen, J.; Pereira, M.P.; Ständer, S.
Abstract: Background: There are currently no published population‐based data on prurigo and pruritus epidemiology in Germany. Objectives: We present the prevalence, incidence and comorbidity frequency of prurigo and pruritus in Germany. Methods: This was a retrospective healthcare research study based on anonymized routine data from the German health insurance company DAK‐Gesundheit. Evaluations were carried out for 2 006 003 adults who were insured as of 31 December 2010. Prurigo and pruritus diagnoses were based on International Classification of Diseases, Tenth Revision, German Modification (ICD‐10‐GM) codes. Results: Prevalence was determined to be 0.21% (adjusted for sex and age 0.19%) for prurigo and 2.21% (adjusted 2.14%) for pruritus in 2010. The adjusted rates extrapolated to the total German population in 2010 show that 130 685 adults would have received a prurigo diagnosis and 1 461 024 a diagnosis of pruritus. In 2011, incidence of new prurigo and pruritus cases was 0.13% (adjusted 0.12%, extrapolated 77 263 cases) and 1.51% (adjusted 1.46%, extrapolated 978 885), respectively. Adults with prurigo suffered most frequently from hypertension (35.16%), hyperlipidaemia (24.95%) and depression (21.97%); all were reported more frequently in patients with prurigo compared with the general population ( P  < 0.001). Similarly, adults with pruritus suffered most frequently from hypertension (31.28%), hyperlipidaemia (23.52%) and depression (18.91%) compared with patients without pruritus ( P  < 0.001). Conclusions: Our data show that prurigo is a relatively rare but significant disease and that pruritus is frequent and very variable in appearance, and both have a high comorbidity burden.